DETECTION AND TRANSMISSION OF RICE STUNT VIRUS ON CIHERANG AND SITU BAGENDIT VARIETIES - Helina, Selvi; Sulandari, Sri; Hartono, Sedyo; Trisyono, Andi (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Detection and Transmission of  rice stunt virus on Ciherang and Situ Bagendit Varieties. The explosion of brown planthoppers recently has caused reduction of rice production in Indonesia. Brown planthoppers do not only act as pest, but also transmit Rice grassy stunt virus (RGSV) and Rice ragged stunt virus (RRSV). Detection of the existence of the two viruses in rice plants and vector insects is important to be done to ensure that the virus is infected with the vector. The aim of this research is to detect the existence of virus in varieties of Ciherang and Situ Bagendit as a result of transmission in the laboratory and to find out the ability of brown planthoppers to transmit stunt virus to both of the varieties. This research was compiled using Completely Randomized Design (CRD) with 4 treatments, namely healthy rice plants of Ciherang and Situ Bagendit varieties, Ciherang and Situ Bagendit varieties which were infested by brown planthoppers each with 5 repetitions. The parameters observed were incubation period, symptoms, plant height, number of leaves and incidence of disease. The data on plant height, number of leaves and incidence of disease were analyzed using ANOVA and continued with the Least Significant Difference (LSD) test at the level of 5%. The results showed that Ciherang and Situ Bagendit varieties were only positively infected by Rice ragged stunt virus. The results of the rice transmission showed that Ciherang variety had a faster incubation period of 10 DAI while Situ Bagendit was 14 DAI, but the two varieties showed an inhibition of growth in plant height and number of leaves compared to healthy plants with each incidence of 51.3% and 46.3%.